Initial Mediterranean response to major climate reorganization during the last interglacial-glacial transition. (1st July 2019) - Martin-Puertas, Celia; Lauterbach, Stefan; Allen, Judy R.M.; Perez, Marta; Blockley, Simon; Wulf, Sabine; Huntley, Brian; Brauer, Achim
Abstract: Millennial-scale Dansgaard Oeschger (DO) variability at northern high latitudes has influenced climatic and environmental conditions in the Mediterranean during the last glacial period. There is evidence that the hemispheric transmission of the DO variability occurred at the end of DO event 25; however, the exact timing and the trigger that activated the environmental response in the Mediterranean remains incompletely understood. Here, we provide evidence that the clear millennial-scale teleconnection between Greenland and the Mediterranean started at ∼111.4 ka BP and was initiated by a sub-millennial scale cooling in Greenland (GI-25b). High-resolution sediment proxies and the pollen record of Lago Grande di Monticchio (MON), Italy, reflect climatic instability during the last millennium of the last interglacial, which was characterised by a first and short cooling episode (MON 1) at 111.44 ± 0.69 ka BP, coinciding with the Greenland cold sub-event GI-25b in duration and timing (within dating uncertainties). MON and Greenland (NorthGRIP ice core) also agree in recording a subsequent warm rebound phase that abruptly culminated in the stadial MON 2/GS-25, marking the transition into the last glacial period. Our results show that the GI-25b triggered an early environmental response at MON to centennial-scale climate change in Greenland as a prelude to the millennial-scale teleconnection that was maintained during the glacial period. Highlights: Annual-resolution study of the transition from the Last Interglacial period to the last Glacial period. Evaluation of the differences in proxy response to sub-millennial-scale climate variability. Chronological discussion based on comparison of independent chronologies.